Gas hydrate formation and dissociation numerical modelling with nitrogen and carbon dioxide - Smith, C.; Barifcani, Ahmed; Pack, D. (2015)
This work aims at providing experimental data for various methane-based hydrates, namely nitrogen and carbon dioxide gas mixtures with varying concentrations to provide an empirically based hydrate equilibrium model. Acquired using a sapphire pressure – volume – temperature (PVT) cell, this data is used as the foundation for the derivation of a model able to calculate the equilibrium temperature of a nitrogen and/or carbon dioxide diluted methane gas. There are several theoretical predictive models used in software which can provide hydrate formation and equilibrium data, however theoretical models appear to outnumber experimental data and empirical models for which a comparison can be made. The effect of nitrogen and carbon dioxide, a diluent and promotor respectively, on methane hydrate formation and dissociation and their associated pressure and temperature conditions are explored. The hydrate profiles for various gas mixtures containing these gases are presented at pressures ranging between 40 and 180 bara. These hydrate profiles and the model presented were compared to those predicted by hydrate computational software and experimental data from other studies for verification. The derived model proved to be reliable when applied to various gas mixtures at different pressure conditions and was consistent when compared to computational software based on theoretical models. Consistency of methane hydrate formation data was compared to dissociation data proved that the formation temperature is not an accurate representation of the equilibrium temperature. A simple statistical measure revealed the dissociation temperature measurements to be more precise and agreed to a much larger degree with literature.